2005
DOI: 10.1111/j.1399-3046.2005.00426.x
|View full text |Cite
|
Sign up to set email alerts
|

Emotional and behavioral problems after pediatric liver transplantation: A quantitative assessment

Abstract: Several uncertainties regarding psychological problems in children who underwent liver transplantation and the need to differentiate these disturbances from those related to the underlying previous chronic liver disease itself exist. This background triggered the present pilot study to investigate, using quantitative assessment methods, the incidence and the type of emotional and behavioral disturbances after liver transplantation. Sixteen liver transplant recipients (aged 5.7-14.4 yr) and 12 age-matched contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
1
8

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 19 publications
1
23
1
8
Order By: Relevance
“…In addition, 16.3% of these adolescents met full criteria for PTSD, a percentage much higher than general population prevalence estimates. Similarly, Gritti et al (2006) found that, based on maternal responses on the Child Behavior Checklist, pediatric recipients of liver transplants had significantly higher ratings of behavioral problems than age-matched controls with chronic liver disease. More recently, Wu, Aylward, Steele, Maikranz, and Dreyer (2008) found that children and adolescents who had received liver and kidney transplantations evidenced elevated parent-reported symptoms of distress (i.e., internalizing symptoms) relative to the Behavioral Assessment System for Children (BASC; Reynolds & Kamphaus, 1992) normative sample, although the youths themselves reported no such elevations.…”
mentioning
confidence: 93%
“…In addition, 16.3% of these adolescents met full criteria for PTSD, a percentage much higher than general population prevalence estimates. Similarly, Gritti et al (2006) found that, based on maternal responses on the Child Behavior Checklist, pediatric recipients of liver transplants had significantly higher ratings of behavioral problems than age-matched controls with chronic liver disease. More recently, Wu, Aylward, Steele, Maikranz, and Dreyer (2008) found that children and adolescents who had received liver and kidney transplantations evidenced elevated parent-reported symptoms of distress (i.e., internalizing symptoms) relative to the Behavioral Assessment System for Children (BASC; Reynolds & Kamphaus, 1992) normative sample, although the youths themselves reported no such elevations.…”
mentioning
confidence: 93%
“…Nearly (QOL) and that QOL improves with time after transplantation (6)(7)(8)(9)(10)(11)(12). (9,11,13,(17)(18)(19)(20). However, in contradiction with impaired neuropsychological development, it was reported that LT did not greatly affect schooling (7,10,13,17,21).…”
Section: Introductionmentioning
confidence: 99%
“…(9,11,13,(17)(18)(19)(20). However, in contradiction with impaired neuropsychological development, it was reported that LT did not greatly affect schooling (7,10,13,17,21). Most of these pediatric studies were conducted among heterogeneous samples with respect to age and the period since LT, and psychological and social development has often been assessed by parental reports (8)(9)(10)(11)21).…”
Section: Introductionmentioning
confidence: 99%
“…Other centres, however, have reported up to 50% of children having adverse psychological reactions with more than 50% having behavioural or emotional disturbances 114,115 . Gritti et al report decreased total behavioural competency and increased externalizing behaviour including aggression and delinquency with 72% exhibiting immaturity of ego and drives 115,116 . There were also more depressive feelings, anxiety, as well as lower parent reported quality of life than in other chronic illness including kidney transplant survivors 112,115,116 .…”
Section: Specific Aim 4: Neurocognitive Outcomesmentioning
confidence: 99%
“…Gritti et al report decreased total behavioural competency and increased externalizing behaviour including aggression and delinquency with 72% exhibiting immaturity of ego and drives 115,116 . There were also more depressive feelings, anxiety, as well as lower parent reported quality of life than in other chronic illness including kidney transplant survivors 112,115,116 . More studies, especially those with long-term follow up, examining psychosocial function in this population are needed to identify risk factors for developing future psychological problems.…”
Section: Specific Aim 4: Neurocognitive Outcomesmentioning
confidence: 99%